Fifth Grade Students Knowledge of Dental and Oral Hygiene Using Dental Spin Wheels Educational Media (A Study at Kenjeran komplex Elementary School Surabaya) - Syofiah, Nila Izzatus; Hadi, Sunomo; Sugito, Bambang Hadi (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
The high and low value of OHI-S can be influenced by several factors, one of which is the knowledge factor. Knowledge of dental and oral hygiene is one of the ways to avoid oral dental health problems. Because, if the individual’s knowledge is good, then the individual can maintain the cleanliness of his teeth and mouth well. On the other hand, if the individual’s knowledge is lacking, the individual does not take care of the cleanliness of his teeth and mouth. The problem in this study is the high OHI-S score in grade V students of SDN Komplek Kenjeran Surabaya which is caused by low knowledge about dental and oral hygiene. The purpose of this study is to find out the knowledge of students V of SDN Komplek Kenjeran Surabaya about maintaining dental and oral hygiene with the counseling media of the Dental Spin Wheels game. This type of research is descriptive. The sample size in this study consists of 60 students. The data collection method used a questionnaire sheet distributed before and after the educational session. The data analysis technique was based on the questionnaire results by calculating the number of correct answers, dividing by the total number of questions, then converting it into a percentage and presenting it in a table format. The results of the study showed that the results of the Pre-Test conducted before counseling were classified as lacking. Meanwhile, the results of the Post-test carried out after counseling have increased and are classified as good.